The competitiveness of African agriculture: Revisiting trade policy reform in Africa - Bouët, Antoine; Odjo, Sunday P. (International Food Policy Research Institute, 2020)
The objective of this chapter is to respond to the question: what can trade policy do for the competitiveness of African agriculture? In the pages that follow, we identify what trade reform consists of, review agricultural policies and market access for African economies, and provide a measure of agricultural competitiveness before summarizing our conclusions.